Religious Diversity, Popular Religions and Multiple Modernities - Parker-Gumucio, C (Oxford University Press, 2020)
Religious diversity and pluralism are increasing in Latin America. The religious field that some decades ago was mainly Catholic has changed radically. In addition to Pentecostalism and Neo-Pentecostalism, other Evangelical as well as independent churches of various denominations and forms, non-affiliated believers, and many diverse (ethnic, Afro-American, New Age, etc.) and diffuse religious expressions are growing. These religious changes toward pluralism can be understood from a revised theory of multiple modernities. The classical sociological concepts and theories, beginning with secularization, need to be criticized and replaced with a new theoretical approach. Latin American historical processes must be compared with what is happening in other regions of the world and not only with Western history. To understand key changes, popular religions worldwide need to be carefully analyzed. Latin American religions offer a good example of popular forms of religious revitalization that are useful to contrast with the Northern European case. This comparative exercise demonstrates new ways of producing sense and spiritual search in non-Western geocultural areas that are framing specific relationships between religion and modernities, bringing about new religious pluralisms. © Oxford University Press 2021.